The effect of water content on increasing grammage in paper made from water hyacinth and cassava peel - Sariah, Jati Nur; Jumiati, Ety; Lubis, Ridwan Yusuf (Universitas Riau, 2024)
Paper is a thin sheet-shaped material containing cellulose from wood. The high demand for paper makes the raw material for paper production increase, which causes forest exploitation. As for this study to determine the effect of mixed variationsin the mixture made from ater hyacinth and cassava peel with the adition of NaOH solution, the characteristics of the paper produced, and the optimal paper quality. Variations in the percentage of water hyacinth and cassava skin raw materials, namely: sample A 30% : 70%, sample B 50% : 50%, and sampel C 70% : 30%. Using the experimental method is done with the soda process. The characterization tests carried out were grammage and water content. The results of the characteristictest obtained grammage values in sample A = 51.6 g/m2, sample B = 84.0 g/m2, sample C = 97.0 g/m2. Test the water content in sample A = 5.7%, sample B = 5.9%, and sample C = 6.1%. Has met the value of SNI 7274-2008 for printing type A paper.